A organização social das inovações técnicas dos agricultores da Associação dos Agricultores Ecologistas de Ipê e Antônio Prado (Aecia) - RS - Moura, Luciane D'avila de (2008)
Place and Date of the Defense: Santa Maria, August 29th of 2008. The question of setting up an appropriate strategy for the promotion of technical innovation composes a key element for social actors who are committed to the processes of agroecological transition. Although it is possible to find references which are relatively consolidated, through the propositive point of view, there is a small amount of knowledge about the arrangement that takes the social organization of innovation that sustains the agroecological transition in concrete experiences. In that sense, this present paper proposes to investigate this issue in the actuation of the Association of ecological farmers of Ipê and Antônio Prado (AECIA), in Rio Grande do Sul RS, appealing the consultation of documents and other studies, participant observation and interviews with agents of NGO and farmers. The results suggest that the introduction of ecological farming interferes in the sphere of social relations, more specifically in the social arrangement of production, making to emerge a new configuration in terms of social organization of technical innovation and creating specific sociotechnical spaces to meet the necessities of these actors, since these actors that maintain the model of industrial agriculture are not able to carry out these new demands.